Feedback from each retinal neuron population drives expression of subsequent fate determinant genes without influencing the cell cycle exit timing. Issue 13 (1st March 2016) - Kei, Jeremy Ng Chi; Dudczig, Stefanie; Currie, Peter D.; Jusuf, Patricia R.
ABSTRACT: During neurogenesis, progenitors balance proliferation and cell cycle exit together with expression of fate determinant genes to ensure that the correct number of each of these neuron types is generated. Although intrinsic gene expression acting cell autonomously within each progenitor drives these processes, the final number of neurons generated is also influenced by extrinsic cues, representing a potential avenue to direct neurogenesis in developmental disorders or regenerative settings without the requirement to change intrinsic gene expression. Thus, it is important to understand which of these stages of neurogenesis are amenable to such extrinsic influences. Additionally, all types of neurons are specified in a highly conserved histogenic order, although its significance is unknown. This study makes use of conserved patterns of neurogenesis in the relatively simple yet highly organized zebrafish retina model, in which such histogenic birth order is well characterized. We directly visualize and quantify birth dates and cell fate determinant expression in WT vs. environments lacking different neuronal populations. This study shows that extrinsic feedback from developing retinal neurons is important for the temporal expression of intrinsic fate determinants but not for the timing of birth dates. We found no changes in cell cycle exit timing but did find a significant delay in the expression of genes driving the generation only of later‐ but not earlier‐born cells, suggesting that the robustness of this process depends on continuous feedback from earlier‐formed cell types. Thus, extrinsic cues selectively influence cell fate determinant progression, which may explain the function of the retinal histogenic order observed. J. Comp. Neurol. 524:2553–2566, 2016. © 2016 Wiley Periodicals, Inc. Abstract : From in vivo time‐lapse imaging and birth dating experiments in zebrafish, this study investigates the highly conserved birth order of different neuron types during retinogenesis and shows that loss of neuron populations delays the expression timing of fate determinant genes important for subsequent neural fates without changing cell cycle timing of progenitors.